Tingkat Pengetahuan, Beban Kerja, Pengawasan, dan Penerapan SOP dengan Kejadian Kecelakaan Kerja di PT X - Mila Amelia Putri; Ahmad Irfandi; Namira Wadjir Sagadji; Mayumi Nitami (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2024)
There were 19 instances of working accidents in 2023, according to PT X's data on workplace incidents. The results of the root cause analysis showed that a lack of understanding of workplace safety, heavy workloads, insufficient supervision, and a failure to follow safety operating procedures (SOPs) were the main causes of workplace accidents. The aim of this research is to ascertain the correlation between PT X employees' knowledge levels, workloads, supervision, and SOP implementation and workplace accidents. Analytical survey research using a cross-sectional study methodology is what this study is. There are 449 production workers in the electrical guitar sector, making up the study's population. Based on the Lemeshow approach, a sample size of 77 workers was determined. A basic random sampling methodology is combined with probability sampling as the sampling method. Chi-square tests and prevalence ratios were used to examine the data. The findings indicate a correlation between workload and workplace accidents (p-value 0.006 < 0.05), knowledge level and workplace accidents (p-value 0.001 < 0.05), workplace accidents and supervision (p-value 0.007 < 0.05), and workplace accidents and the application of SOPs (p-value 0.001 < 0.05). It is possible to draw conclusions from these findings regarding the correlation between PT X employees' knowledge levels, workloads, supervision, and SOP implementation and workplace accidents.